Initiation of Activation of a Preemergent Herbicide by a Novel Alkylsulfatase of Pseudomonas putida FLA - Lillis, Veronica (1983)
The activation of the preemergent herbicide 2-(2,4-dichlorophenoxy)ethyl sulfate (Crag herbicide) is initiated by soil microorganisms that are presumed to act by removing the ester sulfate group via some type of sulfatase enzyme. An enrichment technique with the herbicide as the sole source of sulfur led to the isolation of several pure cultures that could produce 2-(2,4-dichlorophenoxy)ethanol from the herbicide. One of these, a strain of Pseudomonas putida, was particularly active. Polyacrylamide gel zymograms of extracts of cells grown on nutrient broth showed the presence of three secondary and three primary alkylsulfatases. One of the latter enzymes was active toward Crag herbicide as well as sodium dodecyl sulfate. Maximum activity was obtained in the late-stationary phase of growth, and enzyme yields were not affected by either the presence or the absence of the herbicide in the growth medium. The enzyme was purified 2,670-fold to homogeneity by a combination of streptomycin sulfate treatment, heat treatment, and column chromatography on DEAE-cellulose, Sephacryl 200-S, and butyl agarose. The pure enzyme was tetrameric (molecular weight, 295,000) and most active at pH 6.0. Saturation kinetics with inhibition by excess substrate were observed for Crag herbicide and octyl sulfate. 2-Butox-yethyl sulfate was a relatively poor substrate, and dodecyltriethoxy sulfate was not hydrolyzed at all. Enzymatic hydrolysis of each substrate in the presence of H(2)(18)O led to incorporation of (18)O exclusively into SO(4)(2−) ions in all three cases. The Crag herbicide sulfatase therefore acts by cleaving the O-S bond of the C-O-S ester linkage, in contrast with other alkylsulfatases acting on long-chain alkyl sulfates.